Acclimation of Photosynthesis to Changes in the Environment Results in Decreases of Oxidative Stress in Arabidopsis thaliana - Karim, Mohd Fauzihan; Johnson, Giles N. (Frontiers in Plant Science, 2021)
Dynamic acclimation of photosynthesis plays an important role in increasing plant fitness under variable light environments. Acclimation is mediated by a glucose-6-phosphate/phosphate translocator, GPT2. This study examined whether plants lacking GPT2, which are defective in acclimation to increases in light, are more susceptible to oxidative stress. To understand this, we used the model plant of Arabidopsis thaliana (accession Wassilewskija-4 (Ws-4)) and compared this to mutants lacking GPT2. Plants were grown at low light (100 μmol m−2 s−1) for 7 weeks. For acclimation experiments, a set of plant from low light was transferred to 400 μmol m−2 s−1 for 7 days. Biochemical and physiological analyses also showed that the gpt2 mutant plants had significantly greater activity for ascorbate peroxidase (APX), total peroxidase activity (GPOX) and superoxide dismutase (SOD) and significantly lower maximum quantum yield of photosynthesis (Fv/Fm). Microarray analysis showed that gpt2 plants showed a greater induction of stress related genes relative to WT. We conclude that photosynthetic acclimation to a higher intensity of light protects against oxidative stress.